A multicentre RCT on community occupational therapy in Alzheimer's disease: 10 sessions are not better than one consultation. Issue 1 (9th August 2011) - Voigt-Radloff, Sebastian; Graff, Maud; Leonhart, Rainer; Schornstein, Katrin; Jessen, Frank; Bohlken, Jens; Metz, Brigitte; Fellgiebel, Andreas; Dodel, Richard; Eschweiler, Gerhard; Vernooij-Dassen, Myrra; Olde Rikkert, Marcel; et al.
Abstract : Objective: To compare the benefits and harms of a Dutch 10-session Community Occupational Therapy programme for patients with Alzheimer's disease with the impact of a one session consultation at home in German routine healthcare. Design: A seven-centre, parallel group, active controlled randomised controlled trial. Patients and carers were not masked. Assessors were fully blind for treatment allocation for one of two primary-outcome measurements. Setting: Patients' homes. Participants: Patients with mild to moderate Alzheimer's disease (Mini-Mental State Examination 14–24), living in the community with primary carer available and without severe depression or behavioural symptoms, were eligible. Interventions: Experimental 10 home visits within 5 weeks by an occupational therapist, educating patients in the performance of simplified daily activities and in the use of aids to compensate for cognitive decline; and educating carers in coping with behaviour of the patient and in giving supervision to the patient. Control one home visit including individual counselling of patient and carer and explanation of a leaflet on coping with dementia in daily life. Outcome measures: The primary outcome was the patient's daily functioning measured with the Interview of Deterioration in Daily activities in Dementia and the Perceive, Recall, Plan and Perform System of Task Analysis. Assessments were at baseline, 6, 16 and 26 weeks, with a postal assessment at 52 weeks. Results: 141 patients were 1:1 randomised to the experimental (N=71) and control group (N=70). Data for 54 and 50 participants were analysed. Patients' daily functioning did not differ significantly between the experimental and control group at week 6, 16, 26 or 52 and remained stable over 26 weeks in both groups. No adverse events were associated with the interventions. Conclusions: In German healthcare, a Dutch 10-session community occupational therapy was not better than a one-session consultation for the daily functioning of patients with Alzheimer's disease. Further research on the transfer of complex psychosocial is needed. International Clinical Trials Registry Platform: DRKS00000053; Funded by the German Federal Ministry of Health.